APLIKASI METODE PELINEARAN EKSAK UMPAN BALIK PADA PENGENDALIAN SIKAP SATELIT - UTAMI ADININGSIH, NENI
Exact feedback linearization method is an alternative method of a nonlinear system linearization. Since it is an exact transformation, the system perfomance of the linearized system will be so close to the perfomance of the system. The exact feedback linearization uses differential geometry theory to transform a nonlinear functional into a new linear function. It can be done by looking for the input-output relation. This relation can be found by a recursive differentiations at a nonlinear system's output equation and to obtain a new set of equations called normal form of state equations. In this form the linear control law can be applied. This thesis discusses the application of this method for a geostationary satellite control with three-axes stabilization. The angular position of the body described by Gibbs vector. The method used in designing satellite attitude controller is optimal regulator control with quadratic index perfomance with normal (Gaussian) distribution disturbance. The transformation process is analized and a comparative simulation study on the method of Taylor's is given. Generally show that attitude control system that linearized by exact feedback linearization better than the system that linearized by Taylor linearization.